A novel method for load line displacement rate partitioning in creep crack growth tests on Type 316H stainless steel. (January 2020) - Jones, M.D.; Dean, D.W.; Hughes, D.; Davies, C.M.
Highlights: New method of creep crack growth test analysis. Advanced estimates of creep contribution to load line displacement measurements. Analysis method accounts for stress relaxation and strain history effects. Abstract: Characterising the creep crack growth behaviour of Type 316H stainless steel is vital in obtaining accurate predictions for the lifetime of high temperature components, for example in UK advanced gas cooled reactors. The correlation between creep crack growth rates and the fracture mechanics parameter C ∗, considered to govern the crack growth process, is obtained from creep crack growth tests. The C ∗ parameter is experimentally determined using an expression which requires knowledge of the load line displacement rate due to creep. Historically this has been calculated by subtracting values for the elastic and plastic contributions to the load line displacement, obtained from available solutions, from the total experimentally measured load line displacement. However, the solutions available to determine the plastic contribution rely on generating a power-law fit to uniaxial tensile data, which is difficult to accomplish accurately over a large stress range. In addition, these expressions cannot account for strain history effects during crack growth. Consequently the elastic and plastic contributions are often erroneously large and can even be in excess of the experimental total load line displacement. A novel technique has been proposed to provide improved estimates of the creep contribution to the load line displacement rates during creep crack growth tests. This technique employs finite element analysis that incorporates material specific uniaxial tensile test data to simulate crack growth in an experimental test. A single elastic-plastic-creep simulation is used to determine the separate elastic-plastic and creep contributions to the load line displacement, meaning that, unlike historic analyses, creep stress relaxation and strain history effects can now be accounted for. The results have demonstrated that advanced predictions of the creep contributions to the load line displacement can be obtained using this technique.